Responsiveness to robots: effects of ingroup orientation & communication style on hri in china - Wang, Lin; Rau, Pei-Luen Patrick; Evers, Vanessa; Robinson, Benjamin; Hinds, Pamela (Proceedings of the 4th ACM/IEEE international conference on Human robot interaction, 2009)
This study investigates the effects of group orientation and communication style on Chinese subjects' responsiveness to robots. A 2x2 experiment was conducted with group orientation (ingroup vs. outgroup) and communication style (implicit vs. explicit) as dimensions. The results confirm expectations that subjects with a Chinese cultural background are more responsive to robots that use implicit communication styles. We also found some evidence that subjects were more responsive when they thought of the robot as an ingroup member. These findings inform the design of robots for use in China and countries with similar cultural values and reinforce the importance of culturally sensitive design in HRI.